MODEL NATIVIS LANGUAGE ACQUISITION DEVICE (SEBUAH TEORI PEMEROLEHAN BAHASA) - Hasanah, Mamluatul (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2006)
The ability of using mother tongue has been possessed by every child. They can master the language without getting specific education. In a short time a child has mastered the language to communicate with others. There are many theories of language acquisition. One of them that still exists is The Native Model of Language Acquisition (LAD). This theory was pioneered by Noam Chomsky. In this language naturally. This ability develops automatically when the language is used is Language Acquisition Device (LAD). LAD constitutes a hypothesis of feature of grammatical rules used progressively by a child in accordance with his psychological development.